Theoretical Chemical Engineering Modeling and Simulation - Boyadjiev, Christo. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This survey presents the theoretical methods of chemical engineering for modeling and simulation of industrial processes. On this base it is possible to formulate correct experimental conditions and to understand rightly the experimental results. The book uses the mechanics of continuous media approach for modeling of the simple processes as hydrodynamic processes, mass and heat transfer processes. The theory of the scalar, vector and tensor fields permit to create the basic equations and boundary conditions. The problems of rheology, turbulence, turbulent diffusion and turbulent mass transfer are examined too. The book incorporates a lot of fundamental knowledge, but it is assumed that the readers are familiar with the mathematics at engineering level and that they thought some special topics in usual university courses. It includes examples at the end of all chapters using the authors investigations. Therefore, it is highly valuable for scientists as well as graduate and PhD students.